Association between social capital and oral health among adults aged 50 years and over in China: a cross-sectional study - Suyang Li; Yanfei Guo; Junmei Miao Jonasson (BMC, 2022)
Abstract Background Social capital has a potential effect in protecting oral health among population. However, no study has explored the association between social capital and oral health in the Chinese context. Due to the unique culture, political, social context in China, it is important to understand their association in the Chinese context. The study aims to investigate the association between cognitive and structural dimensions of social capital with edentulism among adults aged 50 years and over in China. Method The study used data from the WHO SAGE (Study on Global AGEing and Adult Health) wave 1 China component. Structural social capital was operationalized as social participation. Cognitive social capital was operationalized as perceived community trust and perceived community safety. Community-level social capital was measured by aggregating individual-level social capital into community level. Oral health was measured using a final marker of oral health status, self-reported edentulism. A 2-level multilevel logistic regression was used to evaluate the association between different dimensions of social capital and oral health. Results In total, 12,856 individuals were included in the study, the overall prevalence of edentulism was 9.1% (95% CI 8.3-10.0). Multilevel logistic analysis revealed that individual-level social capital and community-level social capital are independently associated with edentulism. Individuals with low structural social capital and living in areas with low structural social capital have, respectively, 1.54 (95% CI 1.18-2.01) and 2.14 (95% CI 1.47-3.12) times higher odds for edentulism, after adjustment for potential confounders (age, sex, marital status, residence locality, wealth, education level, chronic conditions) and a potential mediator(smoking). Conclusions Living in a community with lower structural social capital and individual with low structural social capital is associated with higher risk for edentulism among adults aged 50 years and over in China.